The use of long head biceps tendon autograft for massive rotator cuff tears: a PRISMA compliant systematic review. Issue 1 (15th October 2022) - Aicale, Rocco; Poeta, Nicola; Savarese, Eugenio; Bernardini, Giulio; Oliva, Francesco; Maffulli, Nicola
Abstract: Introduction: Rotator cuff tears (RCT) are a common cause of shoulder pain and disability, with massive RCT accounting for 10–40% of all rotator cuff tears. Sources of data: A systematic search of PubMed and Scopus electronic databases was performed up to August 2022, and a total of 17 scientific articles were included in the present PRISMA compliant systematic review. Areas of agreement: Understanding the geometric patterns in RCT is essential to achieve appropriate repositioning of the injured tendons in their anatomic location. The long head of the biceps tendon (LHBT) is usually exposed when defects of the anterolateral corner are present and can be easily used to augment rotator cuff repairs. Areas of controversy: There are no definite guideline regarding the management of massive rotator cuff tears. Growing points: The use of LHBT graft is safe and effective, but technically demanding. All studies were level IV articles of medium to high quality. Areas timely for developing research: Prospective long term follow-up studies and randomized controlled trials are needed, adding imaging evaluation and appropriate clinical outcome measures at follow-up.